2020
DOI: 10.1021/acsnano.0c01463
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reduction of Thermal Conductivity in Amorphous Silicon Nitride-Containing Phononic Crystals Fabricated Using Directed Self-Assembly of Block Copolymers

Abstract: Studies have demonstrated that the thermal conductivity (κ) of crystalline semiconductor materials can be reduced by phonon scattering in periodic nanostructures formed using templates fabricated from self-assembled block copolymers (BCPs). Compared to crystalline materials, the heat transport mechanisms in amorphous inorganic materials differ significantly and have been explored far less extensively. However, thermal management of amorphous inorganic solids is crucial for a broad range of semiconductor device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Al pads with thickness of 130 nm are deposited on the center and the edge of the suspended bridge structure for the thermal transport measurements. Detailed information on experimental fabrication processes is discussed in the "Fabrication of PnCs” section and in our recent report ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Al pads with thickness of 130 nm are deposited on the center and the edge of the suspended bridge structure for the thermal transport measurements. Detailed information on experimental fabrication processes is discussed in the "Fabrication of PnCs” section and in our recent report ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent theoretical works of Larkin et al [17] and Zhou et al [18] have shown that propagons in amorphous silicon (a-Si) can have long MFPs that range from tens of nanometers to several micrometers, and thus propagons could contribute to about 40% of the total κ of the bulk [17,18]. Experimental works favor their theoretical analysis, in which 50% of κ reduction has been reported in the cross-plane direction of a-Si thin films [19] and in-plane directions of suspended nanostructures [20][21][22]. These findings strongly suggest that propagons in fact are able to contribute to a relatively large part of the total κ of amorphous, and thus should be considered when analyzing the heat conduction, despite their small density of states.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Fortunately, the self-assembly of BCPs provides a simple, convenient, and lowcost strategy to construct photonic nanodevices with a variety of complex architectures. Currently, two specific routes have been broadly adopted: BCP co-assembly (Hoheisel et al, 2015;Sarkar and Alexandridis, 2015;Stefik et al, 2015) and BCP templating (Kim et al, 2016;Hulkkonen et al, 2018;Zhou et al, 2020).…”
Section: Photonic Nanodevicesmentioning
confidence: 99%